Nature's yield and wonders of art (NYAWA) '13 insect (Penerbit Universiti Putra Malaysia, 2013)
The inaugural Nature's Yield and Wonders of Art (NYAWA) '13: insect is an indexed exhibition that unveils a collection of artefacts from different perspectives of insects' ecosphere and its wonders.